Recursive right-tailed unit root tests for an explosive asset price bubble - Harvey, David I.; Leybourne, Stephen J.; Sollis, Robert (Oxford University Press, 2015)
In this article, we compare the local asymptotic and finite sample power of two recently proposed recursive right-tailed Dickey–Fuller-type tests for an explosive rational bubble in asset prices. It is shown that the power of the two tests can differ substantially depending on the location of the explosive regime, and whether such a regime ends in collapse. Since this information is typically unknown to the practitioner, we propose a union of rejections strategy that combines inference from the two individual tests. We find that, for a given specification of the explosive regime, the union of rejections strategy always attains power close to the better of the individual tests considered. An empirical illustration using the Nasdaq composite price index is also provided.